Study guides

☆☆

Q: How do you factor 49x squared minus 84x plus 36?

Write your answer...

Submit

Still have questions?

Related questions

(7x + 8)(7x - 9)

(-7x + 3)(-7x +3)

(3x - 8)(8x + 5)

It equals 53X- a number is squared when it is multiplied by itself, so 7X by 7X = 49X. 2X by 2X =4X, so 49X + 4X is 53X.

(7x + 6)(49x^2 - 42x + 36)

It is a quadratic expression and it is (7x+6)(7x+6) when factored

4x2+49x+90 = (4x+9)(x+10) when factored

7x2+49x+84 = 0 Divide all terms by 7: x2+7x+12 = 0 Factorize: (x+3)(x+4) = 0 Therefore the x intercepts are -3 and -4

7x2+49x-42 = 7(x2+7x-6)

49

(7x + 4)(49x^2 - 28x + 16)

49x

That doesn't look quite right. As written, that's 4x + 61, which doesn't factor. If you meant 4x2 + 49x + 12, the answer is (4x + 1)(x + 12)

49x.

49x²+70x+25 = (7x+5)² since the root (-70/(2*49)) of the quadratic equations is -5/7 (discriminant = 70²-4*49*25 = 0)

49x^2 + 77x + 30 Improved answer: 7x+57x+6 When simplified: = 64x+6

98x

Pi Ok, it really cannot be answered without knowing to what it is equal and to which form of the equation you are referring: (7x)^2 - 14x = 49x^2 - 14x =7(7x^2 - 2x) or 7(x^2) - 14x = 7(x^2 - 2x)

One can purchase a used HP 49X from the Amazon Marketplace on the Amazon website. One may also find a used HP 49X for sale via the eBay website although this is dependant on individual users wanting to sell their items.

7x - 1 + 49x = 343If this is what you are implying, then:Simplify:56x - 1 = 343Add 1:56x = 344Divide by 56:x = 344/56 = 43/7 = 6.(142857) repeating at period 6.However, if you meant:7(x - 1) + 49x = 343Then divide by 7:x - 1 + 7x = 49Add 1:8x = 50Divide by 8:x = 50/8 = 25/4 = 6.25.

You need at least two terms to find a GCF.

63

I think you are asking about (-7x)^2 multiplied by x^2. The WikiAnswers notation does not allow all the characters so it is sometimes hard to tel If so, we first multiply the things in parentheses since that is what order of operations rules, PEMDAS, tells us. That would be 49x^2, now multiply that by x^2 and we have 49x^4

The area of square is : 49.0

-8 + 7(6x) + 3 = -7x - 5 - 1-8 + 42x + 3 = -7x - 5 - 142x - 8 + 3 = -7x - 5 + (-1)42x - 5 = - 7x - 642x + 7x - 5 + 5 = - 7x + 7x - 6 + 549x = -149x/49 = -1/49x = -1/49